Statistics of the Tropopause Inversion Layer over Beijing - 卞建春 陈洪滨 (Advances in atmospheric sciences, 2008)
High resolution radiosonde data from Beijing, China in 2002 are used to study the strong tropopause inversion layer （TIL） in the extratropical regions in eastern Asia. The analysis, based on the tropopause- based mean （TB-mean） method, shows that the TIL over Beijing has similar features as over other sites in the same latitude in Northern America. The reduced values of buoyancy frequency in 13-17 km altitude in winter-spring are attributed to the higher occurrence frequency of the secondary tropopause in this season. In the monthly mean temperature profile relative to the secondary tropopause, there also exists a TIL with somewhat enhanced static stability directly over the secondary sharp thermal tropopause, and a 4 km thickness layer with reduced values of buoyancy frequency just below the tropopause, which corresponds to the 13-17 km layer in the first TB-mean thermal profile. In the monthly mean temperature profile relative to the secondary tropopause, a TIL also exists but it is not as strong. For individual cases, a modified definition of the TIL, focusing on the super stability and the small distance from the tropopause, is introduced. The analysis shows that the lower boundary of the newly defined TIL is about 0.42 km above the tropopause, and that it is higher in winter and lower in summer; the thickness of the TIL is larger in winter-spring.